PENGARUH PADES, ALOKASI DANA DESA, DAN DANA DESA TERHADAP BELANJA DESA DI KECAMATAN REJOSO - Widyawati, Agustina Ika (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study is to determine whether there is an influence from village original income, village fund allocation, and village funds to village expenditures in Rejoso District in 2020-2021. The approach used is quantitative along with associative methods along with secondary data sources. The sample of this study used non-probability sampling. The data analysis technique used panel data with STATA 16 software. The results of this study indicate that village original income, village fund allocation and village funds have a partial significant effect on village spending. Village original income, village fund allocation, and village funds simultaneously have a significant effect on village spending. Suggestions from researchers for further research in the observation period added and expanded variables.